2018
DOI: 10.2217/cer-2017-0047
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of therapies in lumbar degenerative disc disease: a network meta-analysis of randomized controlled trials

Abstract: Aim:To compare the efficacy and safety of total disc replacement, lumbar fusion, and conservative care in the treatment of single-level lumbar degenerative disc disease (DDD). Materials & methods: A network meta-analysis was conducted to determine the relative impact of lumbar DDD therapies on Oswestry Disability Index (ODI) success, back pain score, patient satisfaction, employment status, and reoperation. Odds ratios or mean differences and 95% credible intervals were reported. Results: Six studies were incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 44 publications
0
8
0
Order By: Relevance
“…14 Long-term studies have also demonstrated that the likelihood of secondary surgery at adjacent spine segments is higher among patients who undergo fusion than among those who undergo lumbar TDR. 4, [15][16][17][18][19][20][21][22] A recent study showed no significant difference in adjacent segment degeneration rates at 8 years between patients who underwent lumbar TDR (42%) and those who continued with nonsurgical treatment (40%). 23 These data suggest that the progression of adjacent segment degeneration is part of the natural history of DDD but may be accelerated by lumbar fusion.…”
Section: Introductionmentioning
confidence: 99%
“…14 Long-term studies have also demonstrated that the likelihood of secondary surgery at adjacent spine segments is higher among patients who undergo fusion than among those who undergo lumbar TDR. 4, [15][16][17][18][19][20][21][22] A recent study showed no significant difference in adjacent segment degeneration rates at 8 years between patients who underwent lumbar TDR (42%) and those who continued with nonsurgical treatment (40%). 23 These data suggest that the progression of adjacent segment degeneration is part of the natural history of DDD but may be accelerated by lumbar fusion.…”
Section: Introductionmentioning
confidence: 99%
“…There is considerable evidence on the benefits of TDA 10 , 15 ALIF 22 , 23 and hybrid 9 , 21 , 24 , 25 constructs in treating symptomatic DDD with comparison studies showing similar clinical outcomes. 11 , 17 , 23 , 26 – 28 However, there are few long-term studies comparing these procedures with each other.…”
mentioning
confidence: 99%
“…The subset of symptomatic disc degeneration has affected 403 million new patients every year worldwide. The treatments of symptomatic disc degeneration vary from noninvasive (physical therapy, pain medication) to invasive surgical intervention [ 15 ]. Surgical approaches will be associated with risks of the surgery and may derive in repeated surgeries due to the increase in the stress received by the other segments.…”
Section: Introductionmentioning
confidence: 99%